The Current Perception of the Academic Environment from the Economic Field Proposed Changes to Improve the Professional Performances - Văcărescu Hobeanu, Loredana (Journal of Research in Educational Sciences; Vol 2 No 1 (2011): JRES, Volume II, Issue 1(3), Summer 2011, 2011)
The achieved studies in the institutions from the university environment confirm the importance they attach to human resources and their professional performances, having the implemented well-structured systems, in which they manage the specific evaluation methods and techniques. The changes which are suffered by the contemporary society require a continuous process of evaluating the results of the academic body on the pathway of the whole existential flow of the human resources from the institution of higher education, leaving from employment, advancement of teaching positions, having regard to the professional performances and the motivation according to the obtained results.